Optimization of Strong Compressive Strength of Environmentally Friendly Paving Blocks through Substitution of Cow Bone Powder and PET Plastic Waste as Additives - Chayrunnisa, Adelia; Setyaningrum, Aprilia Nur Dwi; Suwarto, Fardzanela; Putri, Dita Mentari (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
Cracks caused by excessive loads that exceed compressive strength remain a major issue when applying paving blocks. This study aims to develop environmentally friendly paving blocks by utilizing PET plastic waste and cattle bone powder as substitute materials, and to evaluate their effect on the compressive strength characteristics of paving blocks. Cattle bone powder was used as a partial cement substitute in proportions of 0%, 15%, 20%, and 25%, while PET plastic waste was used as a partial sand substitute at 0%, 5%, 10%, and 15%, intended to fill micro-voids in the concrete mixture. The paving block samples were rectangular, measuring 20 × 10.5 × 6 cm. Based on compressive strength test results at 7 days, converted to 28 days, the highest strength value was achieved with the mixture containing 15% cattle bone powder and 5% PET, reaching 29.22 MPa—meeting the SNI 03-0691-1996 quality standard for Class B. The lowest compressive strength was recorded in the mixture with 20% cattle bone powder and 15% PET plastic, at 6.89 MPa. The lowest water absorption value was found in the mix with 0% cattle bone powder and 5% PET, at 2.79%, while the highest water absorption occurred in the mixture with 25% cattle bone powder and 15% PET, at 8.06%.